A importância da experimentação no ensino de química: uma experiência em escola que atende alunos do campo no município de Upanema RN - Medeiros, Tatiane Costa de (Universidade Federal Rural do Semi-Árido, 2019)
This paper presents the results of a research about the importance of experimentation in chemistry teaching in a school that receives students from the countryside in the town of Upanema RN. As an assumption it is understood that experimentation can become an important teaching strategy to facilitate the learning process of students in that subject. The aim of the research is to understand how chemistry classes are held in a first year high school class and, based on the data obtained, to propose methodologies that value the participation of students and make meaningful learning. The Methodology has a qualitative feature, in which data collection was made through questionnaires with mixed questions, applied to the teacher who teaches in the chemistry subject, as well as to the 41 students in the class under study. After data analysis, it was realized the need to insert experimentation as a motivational resource that favors the contextualization of contents. To facilitate the teacher's work later, the school's chemistry lab was reactivated, organizing the space and drawing up both the safety manual and a notebook with practical lesson guides that could be run in the environment. A demonstrative experimental class was also held, in which some soap was produced by reusing residual cooking oil. It was noticed that the sudents got involved, arousing curiosity on the contents approached with the theme, besides a significant improvement in the number of correct answers to the questions applied before and after the experiment. From these results, it is understood that the experimental activity is still little used in the teachers' methodology as a didactic resource, but its practice provides a better understanding of the chemical concepts and arouses the students interest in the relationship of chemistry with daily life, specifically the countryside
Monografia
Keywords: Experimentação; Ensino de química; Educação do campo; Experimentation; Chemistry teaching; Countryside education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL